Investigation of Various Prediction Models of Demand on the Market of Innovations - Derunova, Elena Anatol’evna; Filatova, Irina Nikolayevna; Semenov, Alexandr Sergeevich; Derunov, Vladimir Alexandrovich (International Review of Management and Marketing, 2017)
The formation of demand forecasting models is important in understanding the transition from the raw to the innovative model of the economy. The aim of the study is to analyze and evaluate the different innovation demand forecasting models and the mathematical substantiation of the directions of their development. On the basis of the Bass model, we explore forecasting the spread of innovative products with the addition of such factors as prices, advertising, and market potential for the purpose of application of applied models in assessing the demand for high-tech products at the market launch of innovative products. Mathematical justification of the problem of demand for high-tech products presented in the context of the theory of diffusion of innovation and developed technique in forecasting of high-tech products sales, which allows in calculating the number of purchases to a specific point in time. A model for innovation demand prediction by logistic regression, which can improve the classification of consumer preferences of high-tech products. Keywords: innovation, sales forecast, marketing high-tech products, consumer behavior, economic growth. JEL Classifications: O, O3, Q55